Dynamics of Domestic Debt and its Implications on Economic Growth: Evidence From SAARC Countries - Muhammad Reehan Hameed; Hafsa Batool; Israr Hussain (Journal of Peace, Development and Communication, 2021)
Due to the fragile tax base and mounting budget deficits South Asian countries are persistently relying on both domestic and external debt which severely affects the growth performance of these countries. The external resources are not easy to get and subject to many constraints while domestic resources are easily accessible. Therefore, the budget deficit is normally financed with domestic debt. This paper examines the short-run and long-run impact of domestic debt on the economic growth of SAARC countries i.e. Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. For the sake of analysis panel data of SAARC countries from 1990 to 2020 has been used. Fixed effect model and panel ARDL econometric techniques have been applied to examine the short-run and long-run association among the variables. The natural log of GDP per capita is used as a proxy for economic growth. The other variables are domestic debt, initial GDP, foreign direct investment, trade openness, investment, and secondary school investment rate. The results of the study indicate that domestic debt has a negative impact on economic growth both in the short-run and long-run. This shows that the domestic borrowed resources have not been utilized effectively and productively. The study suggests that efforts will be made to reduce the budget deficits to minimize the reliance on domestic debt.